Relative Valuation and Quality: Nordic Evidence - Salenius, Eemil (My University, 2020)
This study revisits the value and profitability premiums in the Nordic equity markets and examines whether adding exposure to these both fundamental anomalies simultaneously can improve the performance of a portfolio from using these investing strategies separately. Novy-Marx (2013) finds that quality, measured with gross profitability, can enhance the performance of value investing substantially. Enterprise multiple is a relatively new valuation measure that accounts for operating profitability and is increasingly being used by professionals (Loughran & Wellman 2011). By using enterprise multiple as the valuation measure and conducting the investigation in Nordic markets with a new time period, this study provides an additional contribution to the existing academic literature covering these subjects. First, the value and quality investing strategies are investigated separately to form benchmarks for the comparison of combination strategies. Second, combination portfolios are constructed following methods similar with Fisher, Gregg & Titman (2016). The examined portfolios are constructed using both long-only and long-short approaches although some short-selling and liquidity constraints may occur in Nordic stock markets due to their relatively small size. Results show that both value and quality, measured with enterprise multiple and gross profitability respectively, generated excess average returns over the sample period from January 1991 to December 2019. Combining these strategies to a long-short portfolio by using the average ranking method improved both absolute and risk-adjusted-performance of a portfolio significantly as compared to individual value and quality strategies. Out of the two individual strategies, quality performed better, and its results were driven by both value and growth stocks, suggesting a promising avenue for extended research. Against the initial assumptions, and evidence documented by prior academic literature, growth outperformed value substantially over the sample period. However, the performance was mainly focused on the latter half of the sample period suggesting that investment strategies in general may suffer long periods of underperformance or may even cease to exist. Overall, the returns of different portfolios examined were collectively driven by larger stocks in terms of market capitalizations. The results indicate that investors should especially include the consideration of quality characteristics of a company to their investment analysis process.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance